Season changes in physical performance of youth elite male national team handball players - Povoas, S.; Sampaio, J.; Gomes, I.; Lopes, M.; Goncalves, B.; Marques, M. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction The training of elite handball players should comprise exercises aiming at improving the ability to maintain a high exercise intensity (1,2). Consequently, evaluations should be performed to determine how players are coping with these demands throughout the season. The purpose of this study was to analyse the effects of training and competition during an entire season on the anthropometric and physical profile of elite male youth national team handball players. Methods: Seventeen elite male handball players (under-18) from the Portuguese national team were evaluated at three time points throughout the season (pre-season (T0), competitive period (T1) and immediately before participating in international national teams competitions (T2)). The players performed the Yo-Yo Intermittent Endurance Test.level 2 (YYIE2), the countermovement jump (CMJ), a straight sprint test (5, 10 and 30 m), three sprint tests with changes of direction: forward running (COD), forward/backward running (COD F/B), defensive sideways movements (COD Def), and the running based anaerobic sprint test (RAST). Results: Performance in the YYIE2 increased significantly from T0 to T1 and to T2 time points, and from T1 to T2 in the CMJ, although decreased in the sprint tests from T1 to T2 (p.0.05). A decrease was also shown in COD F/B and COD Def tests from T1 to T2 (p<0.00). There were no significant changes in the anthropometric profile, except for a decrease in fat mass percentage (p=0.05). Discussion: Accordingly to previous studies (3), the results show that training and competition induce alterations in physical performance during a season. Training sessions and competitive matches favourably modified specific endurance and powerrelated abilities throughout the season. The neuromuscular demands of the specific pattern of handball movements and actions did not positively influence COD performance throughout the season in this age group. Since COD movements are required in top elite handball players (1,2), these results suggest that the ability to perform acceleration-deceleration movements, which in turn are associated to eccentric muscle contractions, should be improved in youth players.